3-D Seismic Survey Study of Faults System in Balad Oil Field – Center of Iraq - Al-Ridha, Nawal; Muhsin, Suhail (Iraqi Journal of Science, 2023)
3D seismic reflection structural study of (250) km² of Balad Oil field located in central part of Iraq within Salah Al-din province (Balad area) was carried out.Faults were picked using instantaneous phase attribute of seismic sections and variance attribute of seismic time slices across 3D seismic volume.A Listric growth normal fault is affecting the succession of Cretaceous Formation and cut by strike slip fault. In addition, minor normal faults (Dendritic and tension faults) are developed on the listric normal growth fault. As a result, a major graben is separated by Strike slip fault into two parts (north and south parts) and trend in NW-SE direction.